1998
DOI: 10.1183/09031936.98.12051209
|View full text |Cite
|
Sign up to set email alerts
|

Difficult asthma

Abstract: Asthma is usually easy to manage, but approximately 5% of patients are not controlled even on high doses of inhaled corticosteroids. It is important to assess these patients carefully in order to identify whether there are any correctable factors that may contribute to their poor control. It is critical to make a diagnosis of asthma and to exclude other airway diseases, particularly chronic obstructive pulmonary disease (COPD), and vocal cord dysfunction ("pseudo-asthma"). Poor adherence to therapy, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
165
1
28

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(201 citation statements)
references
References 83 publications
(92 reference statements)
2
165
1
28
Order By: Relevance
“…[25][26][27][28][29] Central to a definition of difficult asthma is, therefore, disease which remains poorly controlled despite medical treatment which would usually be effective. 26,30,31 A more detailed discussion of the concept of difficult asthma is provided in Chapter 2 and part of this review is concerned with further clarification of definitions and indicators for patients at risk from their asthma.…”
Section: Difficult Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29] Central to a definition of difficult asthma is, therefore, disease which remains poorly controlled despite medical treatment which would usually be effective. 26,30,31 A more detailed discussion of the concept of difficult asthma is provided in Chapter 2 and part of this review is concerned with further clarification of definitions and indicators for patients at risk from their asthma.…”
Section: Difficult Asthmamentioning
confidence: 99%
“…2, 26,31 Inevitably, it has profound effects on QoL for patients and prevention of emergency attendances, 32 hospitalisations, 24,33 ICU admissions 14 and deaths 22 associated with difficult asthma represents a challenge to clinicians. Again, although patients with difficult asthma make up a small proportion of the whole population with asthma, they account for a large and disproportionate share of mortality, morbidity and costs.…”
Section: Difficult Asthmamentioning
confidence: 99%
“…5 Multiple studies have shown ICS to improve symptoms and reduce asthma-related morbidity and mortality, [6][7][8] but despite this, a high number of patients being treated according to guidelines remain difficult to control with frequent exacerbations and persisting symptoms. 9 One of the plausible reasons for poorly controlled asthma may be that patients with asthma tend to exhibit poor adherence. 10 Poor adherence to controller medication may lead to a decline in lung function, 11 poor symptom control, 12 and increased risk of asthma-related hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…2 The high percentage of patients not taking their ICS as prescribed also poses a challenge for health-care providers in identifying patients suffering from treatment-resistant or refractory asthma, which is generally defined as asthma not responding to high-dose therapy. 9 This could lead to non-adherent patients being prescribed newer and often more expensive medications, which are reserved for patients with moderate-to-severe asthma who are uncontrolled on high-dose ICS and long-acting ␤ 2 agonists, 14 even though it is likely that they would have achieved comparable asthma control with optimal adherence to ICS instead.…”
Section: Introductionmentioning
confidence: 99%
“…We audited practice records to identify patients with poor control, since poor control is associated with more frequent symptoms and bronchodilator use, and functional impairment, 24,25 as well as poor quality of life. 26 Thus, there is scope for improving asthma management in this group of patients.…”
Section: Recruitment Of Patientsmentioning
confidence: 99%